1979
DOI: 10.1080/17450397909424622
|View full text |Cite
|
Sign up to set email alerts
|

Untersuchungen über die Proteinverdaulichkeit und Aminosäurenresorption in verschiedenen Abschnitten des Verdauungstraktes beim Schwein

Abstract: The crude protein digestibility and the amino acid absorption of six female pigs (average live weight 61 kg) with duodenal and ileocecal re-entrant cannulae, which were fed with a wheat + wheat gluten + lysine ration and an N-free ration, were determined in various segments of the intestines. Comparative experiments concerning the N-metabolism with pigs without and with cannulae showed that the animals renormalised their metabolism 14 days after narcosis and fistulation of the intestines. The extents of secret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1979
1979
1986
1986

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 17 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…Greatest proportional losses of amino acids in the large gut of the sheep are usually incurred with z,6-diaminopimelic acid (DAPA), glutamic acid, valine, alanine, proline, threonine, serine, glycine and cyst(e)ine, in that order (Mason & White, 1971;Coehlo da Silva et al 197za,b;Harrison et al 1973;Hogan, 1973;Ben-Ghedalia et al 1974;MacRae & Ulyatt, 1974;Beever et al 1978), while in the pig the corresponding sequence is found for glycine, glutamic acid, proline, tryptophan, serine, cyst(e)ine and threonine (Holmes et al 1974;Ivan & Farrell, 1976;Mason et al 1976;Sauer et al 19773;Buraczewska et al 1979;Low, 19793). These losses of DAPA, glutamic acid and alanine in the sheep are entirely or partly due to the metabolism of undigested bacterial residues from the upper tract, the latter constituting possibly 25-5070 of the ileal N. The cell-wall DAPA and muramic acid of rumen bacteria resists digestion in the small intestine but is extensively degraded in the hind-gut of this animal (Mason & Milne, 1971;Mason & White, 1971).…”
Section: Vol 43mentioning
confidence: 99%
“…Greatest proportional losses of amino acids in the large gut of the sheep are usually incurred with z,6-diaminopimelic acid (DAPA), glutamic acid, valine, alanine, proline, threonine, serine, glycine and cyst(e)ine, in that order (Mason & White, 1971;Coehlo da Silva et al 197za,b;Harrison et al 1973;Hogan, 1973;Ben-Ghedalia et al 1974;MacRae & Ulyatt, 1974;Beever et al 1978), while in the pig the corresponding sequence is found for glycine, glutamic acid, proline, tryptophan, serine, cyst(e)ine and threonine (Holmes et al 1974;Ivan & Farrell, 1976;Mason et al 1976;Sauer et al 19773;Buraczewska et al 1979;Low, 19793). These losses of DAPA, glutamic acid and alanine in the sheep are entirely or partly due to the metabolism of undigested bacterial residues from the upper tract, the latter constituting possibly 25-5070 of the ileal N. The cell-wall DAPA and muramic acid of rumen bacteria resists digestion in the small intestine but is extensively degraded in the hind-gut of this animal (Mason & Milne, 1971;Mason & White, 1971).…”
Section: Vol 43mentioning
confidence: 99%